Switching to Coformulated Rilpivirine/Emtricitabine/Tenofovir in Virologically Suppressed Patients: Data From a Multicenter Cohort. (1st December 2015) - Pinnetti, Carmela; Di Giambenedetto, Simona; Maggiolo, Franco; Fabbiani, Massimiliano; Sterrantino, Gaetana; Latini, Alessandra; Lorenzini, Patrizia; Ammassari, Adriana; Loiacono, Laura; Bellagamba, Rita; Boumis, Evangelo; Cauda, Roberto; et al.
Abstract : Supplemental Digital Content is Available in the Text.